Extreme reduction of on-resistance in vertical GaN p–n diodes by low dislocation density and high carrier concentration GaN wafers fabricated using oxide vapor phase epitaxy method. (3rd July 2020) - Takino, Junichi; Sumi, Tomoaki; Okayama, Yoshio; Kitamoto, Akira; Imanishi, Masayuki; Yoshimura, Masashi; Asai, Naomi; Ohta, Hiroshi; Mishima, Tomoyoshi; Mori, Yusuke
Abstract: Low dislocation density and low-resistance GaN wafers are in high demand for improving the performance of vertical GaN power devices. Recently, GaN wafers with the dislocation density of 8.8 × 10 4 cm −2 and the resistivity of 7.8 × 10 −4 Ω cm, were fabricated using oxide vapor phase epitaxy (OVPE). In this study, GaN p–n diodes on GaN wafers prepared by the OVPE method were evaluated for verifying their suitability as vertical GaN power devices. An extremely low-differential specific on-resistance of 0.08 mΩ cm 2 and a high breakdown voltage of 1.8 kV were obtained from forward and reverse I – V measurements.